Profitability, Liquidity, Leverage and Firm Size on Dividend Policy - Benyadi Farah Chintya; Hajanirina Andrianantenaina (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This research aims to test whether dividend policy is affected by profitability, liquidity, leverage and firm size. Previous studies findings still need to be reconciled as they are not conclusive (as for Ahmad and Wardani (2014), Kaźmierska-Jóźwiak (2015) and Pinem and Dwi (2016)). This study uses logistic regression to analyse manufacturing companies, listed on Indonesia Stock Exchange. The result of this study showed that profitability and firm size has significantly associated with dividend policy, while liquidity and leverage has not significantly associated with dividend policy. It could help investors to consider firm asset tangibility and its effectiveness to earn profit while deciding to invest in a manufacturing company.